Trade off between Liquidity and Profitability - Sobia Saeed, Hina Mushtaq Anwar F. Chishti, Sumaira Kanwal (International Journal of Scientific Research and Management (IJSRM), 2015)
The study investigates the trade off between liquidity and profitability in the five sectors of Pakistan (Chemical, Fuel & Energy, Paper-Board & Products, Food (Sugar) Sector & Cement Sectors). The central objective is to understand the relationship between liquidity and Profitability in a profit driven Business to the nature and extent of the relationship between them. Further, to find the balance of the conflicting objectives of liquidity and profitability and to determine whether a functional relationship exists between Liquidity & Profitability and then estimate whether or not both reinforce each other or not. Liquidity measures are Current, Quick, Interest Coverage, and Debt to Equity, Creditors, and Stock & Receivables Turnover while the profitability measure was the Return on Assets. Investigation and quantitative analysis methods were used for the study. Analysis is based on data extracted from BSA and the accounts of the companies for the relevant period. Correlation and Panel regression analysis, respectively, are employed to examine the nature and extent of the relationship between the variables and determine whether any cause and effect relationship between them. An Econometric model of perceived functional relationship is specified, estimated and evaluated. Evaluation is based on relevant statistics of Panel regression result. The results show that all the measures of liquidity except Debtors Turnover and Debt to Equity Ratio are contributing positively towards the profitability of the firms. So all these things show that if the firm has sound liquidity, then it will ultimately lead towards the profitability because by this the company would be able to generate the spontaneous financing. However, the findings of this paper are based on a study conducted on the selected company only. Hence, the results are not generalizable to other companies. Secondly, the sample comprises the five sectors. Therefore, the results are valid for those Sectors only.